O Pagador de Promessas: um drama trágico em tempos modernos - Silva, Sebastiana Siqueira e (2009)
This work aims at a critical and interpretative analyses of Dias Gomes dramatic work, the focus of investigation being placed on the social drama O Pagador de Promessas. The theoretical basis for this study departs from the concept of tragedy in the philosophical and literary tradition, considering Aristotle s propositions and his comments on the Greek tragedies in his Poetics. Taking into account that Aristotle defines action as the soul of a tragedy , we focus, initially, on the dramatic categories that emerge as textual elements in the construction of the mythos. These categories, even if originally perceived in relation to the Greek context, were reformulated throughout the centuries, being actualized under new historical perspectives. It was thus that ancient tragedy was transformed into social drama. In modern times, Hegel added to the aristotelean dramatic categories the notion of conflict, thus establishing the basis for a dialectical approach that would be essential to the understanding of both ancient tragedy and modern drama. Hegel s propositions would reappear later in most theoretical and critical studies, among them, in the contributions of Peter Szondi and Raymond Williams, being also present in more recent works by authors we examined, such as Anatol Rosenfeld and Sandra Luna. These theoretical inter-relations were determinant to the critical understanding of Dias Gomes play. Though presenting features of textual composition that enable us to define it as a social drama , O Pagador de Promessas is constructed, in structural terms, as a tragedy , modern as it is, actualizing aesthetic categories of the classical tradition.This play by Dias Gomes incorporates, in the history of Brazilian modern theatre, characters socially placed in so different worlds that the protagonist neither understands now is understood by the other characters of the drama, which leads the hero towards his tragic end. In this plot, the action, constructed on the basis of sharp conflicts of opposed cultures, approaches the fictional text to reality, revealing the social contradictions that shape the characters, providing verisimilitude to the play and forcing the development of an action that is moving, thus producing this modern drama a Kathartic effect that places it closer to the ancient Greek Latin tragedies.